Impact Of Life Style Modifications Among Diabetics in An Urban Slum of Mumbai - Sultan R Ahmad; Gajanan D Velhal; Yasmeen K Kazi (Medsci Publications, 2012)
Purpose: Present study was undertaken to assess the impact of life style modifications and self care practices, among type II diabetics. Methodology: An experimental epidemiological study adopting before and after intervention study design, was undertaken in an urban slum in Mumbai. Representative sample of 200 type II diabetics, received package of interventions along with follow up for 12 months, to assess the impact. Findings: Present study reveals good family support to the patients (90%). Blood sugar, BP, BMI and calories intake decreased significantly after intervention, along with improvement in life style (29% to 40% of patients) and self care practices (1.5% to 15% of patients), with clear difference according to the level of modifications. Major life style modifications and self care practices include spacing of meals, regular exercises, self examination of urine, foot care and carrying biscuits/sugar during traveling. Conclusion: Life style modifications and self care practices promote health of type II diabetics evident by qualitative and quantitative parameters.